Elections and political polarisation: Challenges for environmental agreements - Sarah Spycher (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2024)
This paper examines the role of domestic elections and political polarisation in shaping international environmental agreements and how electoral dynamics may explain the limited success of current climate cooperation. I focus on two key factors: the impact of domestic electoral pressure on international policy decisions and the mismatch between short election cycles and long-term treaty commitments. Using a 4-stage game modelling a bilateral environmental agreement, I analyse how incumbents strategically balance policy preferences with reelection prospects. Results show that while a green incumbent is often forced to temper their ambitions, a brown incumbent faces fewer electoral constraints, explaining why stringent policies are harder to achieve. Nonetheless, electoral pressure can moderate policies, producing outcomes more aligned with the preferences of the median voter. Finally, I discuss how political polarisation, particularly in two-party systems, adds complexity to international cooperation on global public goods.
Keywords: 330; international climate policy; political economy; elections; political polarisation; environmental policy making; public goods; externalities